A Narrative Stylistic Analysis of Associated Press (AP) News - Anisa Choirany; Hermawati Syarif (English Language and Literature, 2020)
Although there have been various stylistic studies of news, the use of narrative stylistic approach in analysing news has not been common. The aim of this research is to analyse the stylistic domains and narrative components in the Associated Press (AP) news. It was carried out descriptive-qualitatively. Ten news were studied by using stylistic units of analysis based on model of narrative structure in Simpson (2004) and Jahn’s classification of narrative components (2005). After completing the analysis, it was found that news is one category of narrative and it contains the use of six stylistic domains and nine narrative components. The six stylistic domains are textual medium, sociolinguistic code, action and event, point of view, textual medium and intertextuality. In addition, there are also occurences of the nine narrative components: narration, focalization, narrative situation, action, story analysis, tellability, tense, time and narrative mode.